Respuesta :

Hey there!

[tex]So\ we\ have\ the\ equation\ \frac{8}{9} (54x - 36)+ 2 = -\frac{3}{4} (-40+16x)+90x\\ First,\ use\ the\ distributive\ value\ to\ eliminate\ the\ parenthesis.  We\ then\ get: \\ 48x - 32 + 2 = 30 + 12x + 90x. \\ Then,\ combine\ like\ terms.\ We\ then\ get: \\ 48x - 30 = 30 + 78x \\Next, \ isolate \ the \variable.\\ 48x-30 = 30 + 78x\\ +30 \to\ both\ sides\\ The\ equation\ becomes: \\ 48x = 60 + 78x\\ Then,\ isolate\ the \ variable. \\  48x - 78x = 60\\ -30x = 60\\ x = -2 [/tex]

Expand by using distributive property

48x - 32 + 2 = 30 - 12x + 90x

combine like terms

48x - 30 = 78x + 30

48x - 78x = 30 + 30

- 30x = 60

    x = -2


ACCESS MORE